2018
DOI: 10.1155/2018/9741838
|View full text |Cite
|
Sign up to set email alerts
|

Using ROS as a Second Messenger, NADPH Oxidase 2 Mediates Macrophage Senescence via Interaction with NF‐κB during Pseudomonas aeruginosa Infection

Abstract: Pseudomonas aeruginosa (PA) is one of the most prevalent pathogens that cause nosocomial infection in critical patients. However, the mechanisms underlying macrophage growth status and functional changes during PA infection are yet unknown. In the present study, NADPH oxidase, gp91phox (NOX2) mediated macrophage to senescence in a PAO1 colony-dependent manner. gp91phox might regulate the senescence process through mutual interaction with the NF-κB pathway. During infection, the overexpression or downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Furthermore, pharmacological inhibition or genetic deletion of gp91 phox similarly reduces NFκB activation, further suggesting NFκB regulation is redox-sensitive and may be directly linked to NOX2 activity. This NOX2-NFκB interaction is corroborated in a Pseudomonas aeruginosa macrophage activation model [ 147 ]. Knockdown of gp91 phox or application of N -acetyl cysteine (the antioxidant, NAC) in infected macrophages reduced NFκB activation levels.…”
Section: Ros Are Secondary Messengers Activating Pro-inflammatory mentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, pharmacological inhibition or genetic deletion of gp91 phox similarly reduces NFκB activation, further suggesting NFκB regulation is redox-sensitive and may be directly linked to NOX2 activity. This NOX2-NFκB interaction is corroborated in a Pseudomonas aeruginosa macrophage activation model [ 147 ]. Knockdown of gp91 phox or application of N -acetyl cysteine (the antioxidant, NAC) in infected macrophages reduced NFκB activation levels.…”
Section: Ros Are Secondary Messengers Activating Pro-inflammatory mentioning
confidence: 74%
“…In neuroinflammatory research, the relationship between oxidative stress and inflammation is a central problem. The two are undoubtedly linked; however, it is not clear how ROS interact with glia to elicit an immune response, although this may involve reciprocal regulation between NOX2 and NFκB [ 147 ]. The mechanisms leading to ROS production and release by microglia have been explored, especially in CAA where NOX activation likely involves fibrin-related clotting factors and IL13 signalling [ 104 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage, which is one of the important immune cells, plays a pivotal role in the regulation of the innate and acquired immune responses [4]. However, the present study showed that macrophages also experience changes due to aging and have an immense influence on immunosenescence [5]. The quantity of aging-related galactosidase-(SA-β-gal-) positive macrophages in the senescence accelerated-prone mice (SAPM8) is considerably larger than that in young mice, and CD36 expression levels and IL-10 level decrease in aging macrophages [6].…”
Section: Introductionmentioning
confidence: 51%
“…Ageing of the immune system predisposed to infection of opportunistic pathogens such as PA 41. In turn, PA infection accelerated cell senescence via NF-κB signaling pathway, which further hampered the eradication of PA 42. Collectively, our findings provide some hints on the complex network underlying the pathogenesis of bronchiectasis associated with PA colonization.…”
Section: Discussionmentioning
confidence: 77%